Intramuscular Microvascular Flow Sensing for Flap Monitoring in a Porcine Model of Arterial and Venous Occlusion - Lu, Di; Moritz, William; Arafa, Hany M.; Yang, Quansan; Jacobson, Lauren; Ostojich, Diana; Bai, Wubin; Guo, Hexia; Wu, Changsheng; Li, Shuo; Li, Shupeng; Huang, Yonggang; Xu, Yameng; Yan, Ying; Westman, Amanda M.; MacEwan, Matthew R.; Rogers, John A.; Pet, Mitchell A. (Journal of Reconstructive Microsurgery, 2022)
Background Commercially available near infrared spectroscopy devices for continuous free flap tissue oxygenation (StO2) monitoring can only be used on flaps with a cutaneous component. Additionally, differences in skin quality and pigmentation may alter StO2 measurements. Here, we present a novel implantable heat convection probe that measures microvascular blood flow for peripheral monitoring of free flaps, and is not subject to the same issues that limit the clinical utility of near-infrared spectroscopy.Methods The intratissue microvascular flow-sensing device includes a resistive heater, 4 thermistors, a small battery, and a Bluetooth chip, which allows connection to a smart device. Convection of applied heat is measured and mathematically transformed into a measurement of blood flow velocity. This was tested alongside Vioptix T.Ox in a porcine rectus abdominis myocutaneous flap model of arterial and venous occlusion. After flap elevation, the thermal device was deployed intramuscularly, and the cutaneous T.Ox device was applied. Acland clamps were alternately applied to the flap artery and veins to achieve 15 minutes periods of flap ischemia and congestion with a 15 minutes intervening recovery period. In total, five devices were tested in three flaps in three separate pigs over 16 vaso-occlusive events.Results Flow measurements were responsive to both ischemia and congestion, and returned to baseline during recovery periods. Flow measurements corresponded closely with measured StO2. Cross-correlation at zero lag showed agreement between these two sensing modalities. Two novel devices tested simultaneously on the same flap showed only minor variations in flow measurements.Conclusion This novel probe is capable of detecting changes in tissue microcirculatory blood flow. This device performed well in a swine model of flap ischemia and congestion, and shows promise as a potentially useful clinical tool. Future studies will investigate performance in fasciocutaneous flaps and characterize longevity of the device over a period of several days.
Keywords: free flap; perfusion monitoring; microsurgery; intramuscular